(untitled) (Journal of the College of Basic Education, 2022)
Mental retardation has attracted the attention of educators around the world for a long time.. It is a phenomenon that pervades all countries of the world and causes problems whose effects are reflected in the health aspects.social and economic. The rate of laggards practically constitutes the equivalent of 31% of the total population inthe world. Interest in the problems of the mentally retarded has increased recently due to the circumstances of the age.industrial sector and the possibility of restoring the ability to work and participate in social activities for a large group ofmentally retarded.” And when 1981 was chosen as the international year “for people with disabilities of all categories (disability(mental - physical - physical) research and studies have been active in every direction to achieve compatibility between the categories ofdifferent disability. Including categories of mentally retarded" who are in need of the cooperation of all the various organs.Thus, the idea of caring for the retarded was crystallized as a human requirement to guarantee the realization of the right of the handicapped tolearning.